The Theoretical Foundations of Evaluation of the Dynamic Efficiency of the Regional Socio-Economic Systems - Fedulova Svitlana O. (Bìznes Inform, 2017)
The article is aimed at determining the applicability of the dynamic standard theory to evaluate the dynamic efficiency of the regional socio-economic systems (RSES). The theoretical and methodical issues of evaluating the dynamic efficiency of the RSES were considered. It is suggested that the theory of «dynamic standard» be taken as a basis. This approach implies a comparison of the existing conditions of system with a particular mode of the reference functioning of economic system. It has been determined that such an evaluation is easy to interpret, allows for compressing a large amount of information on the results achieved, and for a comparative analysis. So, we suggest that the RSES development standard be set on the basis of the indicators dynamics. Considering the dynamics allows distinguishing one development option from another, a certain step from the next or previous one. Constructiveness of this approach to the systemic evaluation of the dynamics of economic systems is determined by the fact that the proposed formal apparatus is based on the principles of dynamic compatibility and dynamic subordination of indicators. These principles can be implemented in most possible cases, as the pace characteristics of the economic dynamics are the inconsistent compared values (the characteristics of economies that are not comparable in statics become comparable in dynamics).